PENGARUH TINDAKAN SUPERVISI PIMPINAN TERHADAP KINERJA PEGAWAI PADA KOMISI PEMILIHAN UMUM DAERAH KOTA TANGERANG SELATAN - Ibrahim Bali Pamungkas; Nanda Rodiyana; Laura Komala (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2021)
The purpose of this study was to determine the supervisory actions of leaders consisting of variables of supervision techniques, supervision principles, supervisor's routine activities, supervision models have a positive and significant effect partially or simultaneously on employee performance. and to find out the most dominant variable of the supervisory technique variable, namely the principle of supervision. , supervisor routine activities, supervision model on employee performance. The result of this study is that there is a positive and significant influence partially or simultaneously between the supervisory actions of the leadership on the performance of the Regional KPU employees in South Tangerang City.